2011
DOI: 10.1111/j.1755-3768.2011.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for trichiasis through a combination of eyelash trephination and electrocautery

Abstract: . Purpose:  This article introduces 3‐mm‐deep eyelash trephination combined with electrocautery as a way to increase the success rate for treatment for trichiasis. Method:  We have modified surgical instruments, ready‐made ophthalmic microtrephine and cautery tip for a 3‐mm‐deep eyelash trephination and electrocautery. After eyelash trephination with microtrephine, electrocautery was added with a bended cautery tip after embedding in the trephination site. The trephined eyelids were photographed biweekly and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…However, repeated radiofrequency treatment is difficult to carry out due to high cost, pain, and other problems that influence the compliance of patients in actual clinical settings. In a recent study on eyelash trephination combined with electrocautery, the success rate was 83% [8], aligning with the success rate (83.6%) of the present study using the simpler additional injection of mitomycin C. In addition, this treatment is anticipated to be effective in reducing postoperative complications that occur due to eyelid injury after radiofrequency treatment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, repeated radiofrequency treatment is difficult to carry out due to high cost, pain, and other problems that influence the compliance of patients in actual clinical settings. In a recent study on eyelash trephination combined with electrocautery, the success rate was 83% [8], aligning with the success rate (83.6%) of the present study using the simpler additional injection of mitomycin C. In addition, this treatment is anticipated to be effective in reducing postoperative complications that occur due to eyelid injury after radiofrequency treatment.…”
Section: Discussionsupporting
confidence: 83%
“…The success rate was reported to be 60% to 67% in a single session of radiofrequency ablation [3,7]. According to a study by Han and Doh [8], the success rate of follicle trephination combined with electrocautery was 83%. Sakarya et al [9] reported success rates of 66.6% in a single session of electrocautery using an ultrafine needle and 100% with two to three sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In horses only cryotherapy and partial tarsal plate excision have been previously described . Cryotherapy and electroepilation are preferred techniques in other species, because these techniques cause less damage to the surrounding structures . In this study, electrocautery was chosen as the treatment modality with a success rate of 50% in other species .…”
Section: Introductionmentioning
confidence: 99%
“…Chirurgische Maßnahmen zur Behandlung dieser Zustände wurden bereits beschrieben, z. B. die Laserkoagulation [6][7][8], Kryotherapie [9], Bestrahlung [10], die Benutzung eines Trepans [11], sowie lidchirurgische Prozeduren mit der Präparation der Wimpernstrukturen mit anschließender Exzision der Follikel [12,13] und schließlich Kombinationen aus den verschiedenen Behandlungen [14][15][16][17]. Wir stellen einen neuen Ansatz dar, welcher es dem Chirurgen erlaubt, den Wimpernapparat in-…”
unclassified